2020
DOI: 10.36478/javaa.2019.260.269
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Nutrient Digestibility and Haematological Parameters of West African Dwarf Goats Fed Water Hyacinth Ensiled with Breadfruit

Abstract: Ruminant animal production in the dry season is usually problematic as weight losses are experienced arising from scarcity of forages. Conservation of Water Hyacinth (WH) (Eicchornia crassipes) ensiled with Breadfruit (BF) can help to bridge this gap. This study investigated the feeding value of WH ensiled with different levels of BF (at 0, 10, 20, 30 and 40% of the total silage diet mixture) as feed for West African Dwarf (WAD) goats. Chopped WH (2-3 cm) and BF were mixed together while sawdust was included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The higher values observed for fecal nitrogen excretion in T2 silage runs contrary to the findings of Idowu et al (2013), who fed graded levels of Toasted Enterolobium cyclocarpum seeds as a supplement to guinea grass. However, results in this study agree with those reported by Akinwande et al (2019), Abegunde & Akinropo (2018), and Mako et al (2012). Nitrogen balance was positive for all diets and therefore suggested that nitrogen absorbed was well tolerated and utilized by goats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher values observed for fecal nitrogen excretion in T2 silage runs contrary to the findings of Idowu et al (2013), who fed graded levels of Toasted Enterolobium cyclocarpum seeds as a supplement to guinea grass. However, results in this study agree with those reported by Akinwande et al (2019), Abegunde & Akinropo (2018), and Mako et al (2012). Nitrogen balance was positive for all diets and therefore suggested that nitrogen absorbed was well tolerated and utilized by goats.…”
Section: Discussionsupporting
confidence: 92%
“…Values observed for nitrogen utilization, nitrogen balance, and nitrogen retention are all related to the amounts of nitrogen ingested and digested (Akinwande et al, 2019). All diets used in this study had positive nitrogen balances, which indicated adequacy in the protein requirement for maintenance (Abegunde & Akinropo, 2018). The values reported for nitrogen intake in this study are lower than those reported by Akinwande et al (2019) for WAD ewes fed ensiled Alternanthera brasiliana (19.05-22.85 g/d) but were higher than those reported by Mako et al (2012) for WAD goats fed guinea grass and varying levels of Acroceras zizanioides (AZ) (3.85 -6.95 g/d).…”
Section: Discussionmentioning
confidence: 85%